Effects of Epigallocatechin-3-gallate (EGCG) on the bond strength of fiber posts to Sodium hypochlorite (NaOCl) treated intraradicular dentin - Yu, Hao-han (Sci Rep, 2017)
This study was to evaluate the effect of Epigallocatechin-3-gallate (EGCG) on the bond strength of two adhesive systems to the Sodium hypochlorite (NaOCl) treated intraradicular dentin. The roots were accepted regular root canal treatments and post space preparations, and further divided into eight groups according to the four post space pretreatments and two dentin adhesives [Single Bond 2 (SB2) and Clearfil SE Bond (CSB)] used. The push-out strength before and after thermocycling in different root region (coronal and apical), DC of the adhesive and morphologic patterns of treated post space were evaluated. NaOCl + EGCG groups showed the highest push-out strength regardless of the adhesive type, root region and time (P < 0.05). NaOCl pretreatment significantly decreased the push-out strengths and DC of CSB (P < 0.05). EGCG could improve the bonding properties of both SB2 and CSB to NaOCl treated intraradicular dentin. The effect of NaOCl on bonding of a fiber post depended on the type of the adhesive.